Pelatihan Pembuatan Aneka Produk Olahan Cabai dan Bawang Merah sebagai Upaya Peningkatan Nilai Jual Hasil Pertanian dan Pemberdayaan Ibu Rumah Tangga Di Kalurahan Bugel, Kapanewon Panjatan, Kulonprogo, DIY - Tien Aminatun; Fitri Rahmawati; Anna Rakhmawati; Rizka Apriani Putri; Budiwati Budiwati; Tutiek Rahayu (Yogyakarta State University, 2023)
Bugel is one of districts in Kulon Progo Regency that uses Surjan Method in planting rice as their local agricultural system. One of major problems faced by the farmer during harvest season is the drop of the yields’price which then lead to the financial loss for the farmers. In order to anticipate the same issue happens in the next harvest season, farmers in subdistrict Bugel, District of Panjaten, Kulon progo Regency want to have a training in regard to process the food such as Red Chilli and Shallot, therefore rotten and damaged yields due to the longer time of storage can be reduced or even avoided. After being processed through the postharvest techniques, those yields are expected to increase in prices thus they will bring profit and more income for the citizens. This training aims to introduce postharvest techniques that can be used to store the yields longer and also to train citizens on food processing which resulted in finer product and ultimately can be sold in higher price. Red Chilli and Shallots are the main yields harvested during the harvest season outside Rice. Two types of Sambal made from red Chilli and processed food of Shallots (Fried Shallot) are made during the practice. These products hopefully will last longer in storage and also can be sold in higher price compared to the fresh ones.Customer satisfactory surveys results showed that attendance were responded positively towards the training. Based on the evaluation, citizens wish for similar training in the future with topic regarding the health and safety of the products as well as the marketing aspect of them.